Impact of sugar-based baits on midgut microbiome composition in Aedes mosquitoes: Implications for vector control - Ranjitha Sambanthan; Nur Faeza Abu Kassim; Sara A. Abuelmaali; Wan Maryam Wan Ahmad Kamil; Sumiyyah Sabar; Kamarul Zaman Zarkasi; Wan Rosli Wan Ishak; Cameron E. Webb (PLoS ONE, 2026)
The Aedes mosquitoes are responsible for the transmission of many severe diseases. Novel integrated vector management techniques like alginate hydrogel beads and appealing toxic sugar bait have strengthened control efforts. These techniques help to control mosquitoes by taking advantage of their attraction to sugar. Different types of sugar that mosquitoes ingest during feeding can affect the makeup of the microbiome in the midgut. The mosquito midgut microbiome maintains immune priming and baseline immune activity. Therefore, the current focus of this study is on utilizing microbial communities for vector control measures with a particular emphasis on how they consume various forms of sugars. Both wild and lab strains of Ae. aegypti and Ae. albopictus mosquito samples were reared, and attractive targeted sugar baits (ATSBs) infused with Chrysanthemum , mango, mix and control solutions. Then, the impact of bacterial communities was assessed using 16S rRNA gene sequences. According to our findings, the majority of the bacterial species in mango and mixed treatments belonged to the Enterobacteriaceae family. A total of 24 different bacterial species were found in Aedes mosquitoes that fed on mango ATSBs. The isolates were found to be members of three phyla from Actinobacteria (4.16%), Firmicutes (54.17%), and Proteobacteria (41.67%). Data reveals that different species, strains, and diets affect the midgut bacterial diversity in the mosquitoes. In addition to strengthening our knowledge concerning the way this bacterium shapes the microbial community, a thorough investigation of the prevalence of the midgut bacterial community is essential for alerting present and future mosquito and disease control initiatives.